2014
DOI: 10.1021/ie403486x
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Mesoporous Zeolite Y with Improved Catalytic Performance for Heavy Oil Fluid Catalytic Cracking

Abstract: A facile and direct approach for the synthesis of mesoporous zeolite Y by using [(CH3O)3SiC3H6N(CH3)2-C18H37]Cl as template is presented. Under the basic condition of the Y synthesis system, (CH3O)3Si– bonds hydrolyze to −Si–OH, and yield −Si–O–Al– and −Si–O–Si– linkages that anchor the template in zeolite framework. Afterward, micelles formed by −C18H37 lead to the formation of mesoporosity within zeolite Y crystals. This material, which introduces intracrystalline mesoporosity into zeolite Y, shows superior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 37 publications
(55 reference statements)
2
36
0
Order By: Relevance
“…Mesoporous Y zeolite can also be obtained using surfactant templates [33][34][35][36][37][38][39][40]. Garcia-Martinez et al reported about the scale-up of a surfactant-templated process to prepare mesoporous Y zeolite; composite catalysts based on such hierarchical zeolite Y showed improved yield of valuable gasoline and light cycle oil (LCO) products over bottoms and coke in FCC catalyst evaluation [41].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mesoporous Y zeolite can also be obtained using surfactant templates [33][34][35][36][37][38][39][40]. Garcia-Martinez et al reported about the scale-up of a surfactant-templated process to prepare mesoporous Y zeolite; composite catalysts based on such hierarchical zeolite Y showed improved yield of valuable gasoline and light cycle oil (LCO) products over bottoms and coke in FCC catalyst evaluation [41].…”
Section: Introductionmentioning
confidence: 99%
“…Garcia-Martinez et al reported about the scale-up of a surfactant-templated process to prepare mesoporous Y zeolite; composite catalysts based on such hierarchical zeolite Y showed improved yield of valuable gasoline and light cycle oil (LCO) products over bottoms and coke in FCC catalyst evaluation [41]. Another versatile method to introduce mesopores in zeolites involves the use of organosilanes that covalently bind to the growing zeolite surface [33][34][35][36][37]. This approach was first described by the Ryoo group in the preparation of mesoporous ZSM-5 [33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the molding principle and characteristics of the ''congenital'' micelle template for the synthesis approach of mesoporous MCM-41 molecular sieve, it determines the amorphous essence of its pore walls, lower structure stability and acidity. Therefore, its application prospect and future development in modern petrochemical industry are restrained greatly [16], especially for the conversion of large molecules as those encountered in heavy crude oil catalytic cracking process [17,18]. In order to overcome limitations of single microporous or mesoporous molecular sieves and to make preponderance complementarity between the two type molecular sieves, some research groups had extended new synthesis strategy to prepare mesoporous SAPO [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%